2022
DOI: 10.3390/plants11212860
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptomic Analysis of Tobacco Leaf with the Functional Loss of the Plastid rpoB Operon Caused by TALEN-Mediated Double-Strand Breakage

Abstract: At least two sets of RNA polymerase (RNAP), nucleus (NEP)- and plastid (PEP)-encoded polymerases, recognizing distinct promoters exist in the plastids of land plants. Most plastid genes are regulated by multiple promoters with different strengths in their response to developmental stages and environmental cues. Recently, we applied chloroplast-targeted transcription activator-like effector nuclease (cpTALEN) technology to site-specifically cause double-strand DNA breaks in the rpoB gene of tobacco, which encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the chloroplast, the large subunit is encoded by RBCL, and it catalyzes two competing reactions, CO 2 fixation in photosynthesis and the production of 2-phosphoglycolate in the photorespiratory pathway [71]. In rice and tobacco, deletion of the rpoA or rpoB encoding the subunits of plastid-encoded RNA polymerase resulted in photosynthetic incompetence [33,72]. In our study, plastid-encoded photosynthesis-related genes showed lower expression levels in the ygl19 mutant.…”
Section: The Mutation Of the Ygl19 Gene Affects The Expression Of Pho...mentioning
confidence: 46%
“…In the chloroplast, the large subunit is encoded by RBCL, and it catalyzes two competing reactions, CO 2 fixation in photosynthesis and the production of 2-phosphoglycolate in the photorespiratory pathway [71]. In rice and tobacco, deletion of the rpoA or rpoB encoding the subunits of plastid-encoded RNA polymerase resulted in photosynthetic incompetence [33,72]. In our study, plastid-encoded photosynthesis-related genes showed lower expression levels in the ygl19 mutant.…”
Section: The Mutation Of the Ygl19 Gene Affects The Expression Of Pho...mentioning
confidence: 46%
“…RPOB is a subunit of chloroplast DNA‐dependent RNA polymerase that affects chloroplast development. The lack of RPOB leads to pale and albino leaf phenotypes in rice and tobacco (Huang et al, 2020; Liu et al, 2022). Several DEGs related to impaired chloroplast complex activity were upregulated in albinism process of ZH2, including PsbP‐DOMAIN PROTEIN 1 (PPD1), PsbQ‐LIKE 2 (PQL2), ATS2, and STN8 (Liu et al, 2012; Schonberg et al, 2017; Suorsa et al, 2010; Yu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The DSB was repaired by homologous recombination (HR) including microhomology-mediated recombination, but not by non-homologous end-joining, which is predominantly observed in the nucleus. The following year, the same group reported analyses on the transcriptome of a heterotrophic albino mutant, in which rpoB1 (a gene of a subunit of the plastid-encoded RNA polymerase) was knocked out by the plastid-targeted TALENs ( Liu et al. 2022 ).…”
Section: Targeted Editing Of the Plastid Genomementioning
confidence: 99%